Tropical cyclone induced compound flooding in Madagascar: A coupled modeling approach - Khan, Md Jamal Uddin; Durand, Fabien; Afroosa, M.; Coulet, Paul; Bertin, Xavier; Mueller, Valerie; Krien, Yann; Wainwright, Caroline (Springer, 2025)
Compound flooding occurs when multiple contributing factors, such as oceanic (storm surge, tide, and waves) and continental (heavy rainfall and river discharge), combine to exacerbate flood impacts. Tropical cyclone (TC)-induced compound flooding is a major hazard and societal concern, particularly in underdeveloped, highly exposed and vulnerable countries like Madagascar. Despite being repeatedly impacted by TCs, the region receives little attention from the scientific community, particularly in the modeling of TC-induced flooding and associated hazards. Here, we developed a high-resolution (30 m) compound flood model over Madagascar. The model is nested in a regional tide-surge-wave model purpose-built for this region. A dedicated topographic and bathymetric dataset was developed to accurately represent the whole land–ocean continuum. Using this framework, we modeled a recent intense TC Batsirai (2022) and assessed the resulting flooding. Our model shows good accuracy, achieving a hit ratio of 0.83 when matched with the remote sensing derived flood map. Our results demonstrate that the TC-induced flooding in this region is compound in nature, with flooding being significantly underestimated when continental factors (e.g. rainfall-runoff) are excluded. The impact of the ocean is primarily observed along the coastline, extending 5–10 km inland along the rivers. Additionally, we identified a non-linear interaction between oceanic and continental factors, which has important implications for the numerical modeling of such compound flood events. We estimate that at least 30% of the flooded area in our modeled domain comprises agricultural lands, highlighting the potential for significant societal impact. The developments and findings of this study pave the path forward for a national-scale compound flood modeling over Madagascar at a resolution suited for household-scale flood risk and impact assessments.